Intracardiac flow dynamics regulate atrioventricular valve morphogenesis. (6th August 2014) - Kalogirou, Stamatia; Malissovas, Nikos; Moro, Enrico; Argenton, Francesco; Stainier, Didier Y.R.; Beis, Dimitris
Abstract: Aims: Valvular heart disease is responsible for considerable morbidity and mortality. Cardiac valves develop as the heart contracts, and they function throughout the lifetime of the organism to prevent retrograde blood flow. Their precise morphogenesis is crucial for cardiac function. Zebrafish is an ideal model to investigate cardiac valve development as it allows these studies to be carried out in vivo through non-invasive imaging. Accumulating evidence suggests a role for contractility and intracardiac flow dynamics in cardiac valve development. However, these two factors have proved difficult to uncouple, especially since altering myocardial function affects the intracardiac flow pattern. Methods and results: Here, we describe novel zebrafish models of developmental valve defects. We identified two mutant alleles of myosin heavy chain 6 that can be raised to adulthood despite having only one functional chamber—the ventricle. The adult mutant ventricle undergoes remodelling, and the atrioventricular (AV) valves fail to form four cuspids. In parallel, we characterized a novel mutant allele of southpaw, a nodal-related gene involved in the establishment of left–right asymmetry, which exhibits randomized heart and endoderm positioning. We first observed that in southpaw mutants the relative position of the two cardiac chambers is altered, affecting the geometry of the heart, while myocardial function appears unaffected. Mutant hearts that loop properly or exhibit situs inversus develop normally, whereas midline, unlooped hearts exhibit defects in their transvalvular flow pattern during AV valve development as well as defects in valve morphogenesis. Conclusion: Our data indicate that intracardiac flow dynamics regulate valve morphogenesis independently of myocardial contractility.